2009
DOI: 10.1186/1471-2164-10-224
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence determination of a novel reptile iridovirus isolated from soft-shelled turtle and evolutionary analysis of Iridoviridae

Abstract: Background: Soft-shelled turtle iridovirus (STIV) is the causative agent of severe systemic diseases in cultured soft-shelled turtles (Trionyx sinensis). To our knowledge, the only molecular information available on STIV mainly concerns the highly conserved STIV major capsid protein. The complete sequence of the STIV genome is not yet available. Therefore, determining the genome sequence of STIV and providing a detailed bioinformatic analysis of its genome content and evolution status will facilitate further u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 58 publications
(57 reference statements)
5
96
0
2
Order By: Relevance
“…As was showed by dot plot analysis, RGV is most closely related to STIV and clusters with ranaviruses with high support, confirming that RGV is a member of the genus Ranavirus. It was also observed that ranaviruses of other subgroups clustered together, i.e., FV3-like viruses (RGV, STIV, FV3, TFV), ATV-like viruses (ATV and EHNV), and GIV-like viruses (SGIV and GIV), which is consistent with previous studies [2,11,35].…”
supporting
confidence: 81%
See 2 more Smart Citations
“…As was showed by dot plot analysis, RGV is most closely related to STIV and clusters with ranaviruses with high support, confirming that RGV is a member of the genus Ranavirus. It was also observed that ranaviruses of other subgroups clustered together, i.e., FV3-like viruses (RGV, STIV, FV3, TFV), ATV-like viruses (ATV and EHNV), and GIV-like viruses (SGIV and GIV), which is consistent with previous studies [2,11,35].…”
supporting
confidence: 81%
“…There is evidence that the ancestral ranavirus was a fish virus and that several recent host shifts have taken place, with subsequent speciation of viruses in their new hosts [11]. Indeed, there is also evidence that ranaviruses switched hosts from tiger salamanders to freshwater sport fish during bait trade [37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RNase III was identified in purified virus particles and infected cells by our proteomic experiments (Table 2; see also Tables S1 and S3 in the supplemental material) and was previously identified in particles of SGIV (31), confirming that this protein is produced and, hence, likely to have a role in IV replication. miRNA has also been predicted for soft-shelled turtle iridovirus (STIV) (18), and the presence of miRNAs has recently been confirmed for SGIV (44).…”
Section: Resultsmentioning
confidence: 99%
“…As an aquatic virus, iridovirus was increasingly taken into account because it caused heavy economic losses in farmed food and ornamental fish, as well as posed great threat to wildlife conservation. The researches about iridovirus focused on complete sequence determination (Eaton et al, 2007;Huang et al, 2009;Jancovich et al, 2010;Shi et al, 2010;Wong et al, 2011;Zhang et al, 2004), transcriptome and proteome analysis Dang et al, 2007;Ince et al, 2010;Luo et al, 2009;Majji et al, 2009;Song et al, 2006) and individual gene identification (Ao and Chen, 2006;Lin et al, 2008;Wan et al, 2010;Wang et al, 2008;Zhao et al, 2007Zhao et al, , 2008b, such as RGV thymidine kinase (TK) gene and envelope protein 53R. TK gene, an early gene of RGV, exists in many large DNA viruses and encodes a cytoplasmic protein .…”
Section: Introductionmentioning
confidence: 99%